(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Surrogacy refers to a practice whereby one woman bears and gives birth to a child for an intended couple with the intention of handing over such a child to the intended couple after birth. The right to parenthood, often referred to as the right to procreate or reproductive rights, is a fundamental human right. It encompasses individuals’ ability to make decisions about having and raising children without undue interference from the state or other entities. This right is rooted in various legal and constitutional principles including the right to privacy, family autonomy, and personal liberty. In this case, we have tried to scrutinize the laws of the surrogacy act and how they impacted the life of an intending couple. The Supreme Court has protected the right of parenthood of a woman suffering from a rare medical condition by staying the operation of a law that threatened to wreck her hopes to become a mother through surrogacy